Coping with frustrated students: main strategies and their interpretation - Bozhok, Natalia (My University, 2013)
In the thesis the psychological reasons for students’ frustrations are considered. The interpretation of coping process in adolescents is presented. The main strategies of coping in adolescence are analyzed.
Keywords: frustration; students; coping; фрустрація; коупінг; студенти; фрустрация; студенты; коупинг; кафедра ділової іноземної мови та міжнародної комунікації